Focal thalamocortical circuit abnormalities in sleep related epilepsy caused by focal cortical dysplasia type II. (July 2022) - Jin, Bo; Zhang, Zheyu; Wang, Chao; Li, Hong; Zhao, Xiaoyu; Wang, Shan; Chen, Cong; He, Chenmin; Zheng, Yang; Geng, Yu; Wang, Shuang; Chen, Guihua; et al.
Highlights: We firstly investigated the thalamocortical circuit in FCD type II with SRE. Thalamocortical circuit to lesion region was different in SER compared to non-SRE. These findings may help to unravel the underlying neuroanatomical character of SRE. Abstract: Purpose To investigate the variations of the thalamocortical circuit between the focal cortical dysplasia (FCD) type II patients with sleep-related epilepsy (SRE) and those without SRE (non-SRE). Methods Patients with epilepsy who had histologically proven FCD type II were enrolled. Those without diffusion tensor image and 3-dimensional (3D) T1 MRI sequences were excluded. Thalamocortical structural connectivity to lesion and non-lesion regions was quantified using probabilistic tractography. Fractional anisotropy (FA) and mean diffusivity (MD) were computed. Results A total of 30 consecutive patients were included. Among them, 18 patients (60%) had SRE. Analysis of covariance showed that smaller lesion size was significantly associated with SRE (p=0.048). Compared to patients with non-SRE, patients with SRE showed a significant decrease in FA of thalamocortical projections to the lesion region (p=0.007). No difference was observed in the thalamocortical connectivity to the non-lesion region between patients with SRE and non-SRE. Among the patients with SRE, a significant decrease in FA of thalamocortical projections to the lesion region was noted compared with the contralateral homotopic non-lesion region (p=0.026). Conclusion The data provide evidence of disparity in thalamocortical projections to the lesion regions between SRE and non-SRE. This might indicate the underlying pathophysiology or neuroanatomical substrates of SRE related to the FCD type II.